Budaya Literasi Dalam Dunia Pendidikan (Studi Kasus Pada Sd Di Provinsi Riau) - Febrina Dafit; Agustiani Agustiani; Nurhafizdah Fitri; Syadidah Khansa Rafikin (Pusat Riset dan Inovasi Nasional, 2023)
One of the biggest challenges in the education system in Indonesia is the lower quality of education. Although the government has implemented various policies to overcome these problems, the results obtained have not shown significant progress. Based on several sources and observations in the field, the low quality of education is caused by the low literacy skills of students in learning and in everyday life. The problem with the quality of education has been exacerbated by the Covid-19 pandemic which has caused